2018
DOI: 10.12820/rbafs.23e0009
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of sedentary behavior in brazilian adolescents

Abstract: The present study objectively measured the pattern of sedentary behavior among schoolchildren from a city in southern Brazil. A probabilistic sample composed of 394 adolescents was selected from ten public schools in the city of Londrina/PR. The cut-point of 720 counts.min -1 for the vector magnitude from the ActiGraph accelerometer was used to estimate the total sedentary time, bouts (1-4 min, 5-9 min, 10-14 min, 15-29 min, and ≥ 30 min), and breaks during the week, on weekdays and at weekends, as well as at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
(30 reference statements)
0
8
0
3
Order By: Relevance
“…The majority of Brazilian studies (approximately 86%) have used subjective measures to evaluate SB through self-reported questionnaires or interviews, which may compromise the quality of the measure, as these methods present less accuracy and poor correlation with device-derived measures 22 . Chastin et al 15 compared several subjective instruments of SB measurement with a device-derived measurement instrument and found that the first present great bias, low precision, and low correlation with the second, besides not presenting standardization between the domains and time reference that they aim to measure. Another point is that although accelerometers have been used in several studies to evaluate SB, the technology of most of the models used does not allow differentiation of postural changes, considering stationary behavior as synonymous with SB, overestimating the measurement, which should only be considered in the sitting, reclined, or lying down positions 1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of Brazilian studies (approximately 86%) have used subjective measures to evaluate SB through self-reported questionnaires or interviews, which may compromise the quality of the measure, as these methods present less accuracy and poor correlation with device-derived measures 22 . Chastin et al 15 compared several subjective instruments of SB measurement with a device-derived measurement instrument and found that the first present great bias, low precision, and low correlation with the second, besides not presenting standardization between the domains and time reference that they aim to measure. Another point is that although accelerometers have been used in several studies to evaluate SB, the technology of most of the models used does not allow differentiation of postural changes, considering stationary behavior as synonymous with SB, overestimating the measurement, which should only be considered in the sitting, reclined, or lying down positions 1 .…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still unclear in the literature how best to measure subjective SB. Depending on the purpose of the research, whether for surveillance or epidemiological surveys, in all domains or specific domains, the manner used to ask the question or the reference time can vary greatly 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,6 A ausência de associação dos breaks com os marcadores cardiometabólicos pode estar relacionada ao fato de os adolescentes acumularem a maior parte do seu tempo diário em comportamento sedentário em blocos de até 5 minutos. 1,14,16 A exposição a blocos de tempo curtos em comportamento sedentário pode minimizar a redução da atividade da enzima LPL (lipoproteína lipase) e contribuir para o aumento do gasto energético. Esses dois fatores estão relacionados com diminuição nos níveis sanguíneos de glicose e triglicerídeos e aumento de HDL-c. 42 O tempo excessivo de comportamento sedentário não moderou a associação entre o número de breaks e…”
Section: Discussionunclassified
“…2,12,13 Estima-se que adolescentes permanecem cerca de 10 horas por dia em comportamento sedentário. 14,15 e 30,2% destes passam mais de 8 horas por dia nesse comportamento. 16 Nesse sentido, a inclusão de interrupções no tempo despendido por dia nesses comportamentos, denominadas breaks, vem sendo considerada como uma das formas de minimizar os efeitos deletérios decorrentes da exposição excessiva e ininterrupta aos comportamentos sedentários.…”
Section: Introductionunclassified